2019
DOI: 10.1101/795005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The SAMPL6 SAMPLing challenge: Assessing the reliability and efficiency of binding free energy calculations

Abstract: Approaches for computing small molecule binding free energies based on molecular simulations are now regularly being employed by academic and industry practitioners to study receptor-ligand systems and prioritize the synthesis of small molecules for ligand design. Given the variety of methods and implementations available, it is natural to ask how the convergence rates and final predictions of these methods compare. In this study we describe the concept and results for the SAMPL6 SAMPLing challenge, the first … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 140 publications
(198 reference statements)
0
30
0
Order By: Relevance
“…that is outside of scope for this work, and (b) details will depend on the exact implementation in those software packages. Previous work has shown that different simulation engines are able to take in the same force field and same systems and give identical energies (with PME) within a reasonable tolerance, which would strongly suggest the implementations are equivalent or nearly so, 111,112 at least for PME.…”
Section: Discussionmentioning
confidence: 97%
“…that is outside of scope for this work, and (b) details will depend on the exact implementation in those software packages. Previous work has shown that different simulation engines are able to take in the same force field and same systems and give identical energies (with PME) within a reasonable tolerance, which would strongly suggest the implementations are equivalent or nearly so, 111,112 at least for PME.…”
Section: Discussionmentioning
confidence: 97%
“…To enable using CD nano-carrier system for a novel class of drugs, one should perform a screening and/or biochemical characterization of potential complexes, which can be a quite laborious and expensive process [28]. Computational methods aim to automatize and reduce the time and cost to discover new drugs [18,15], however, traditional scoring functions (SF), empirical or physics-based, still struggle to rank potential binders, unless rigorous free energy calculations could be performed, this limitation has been addressed in several community challenges [24], highlighting the potential of Machine Learning Scoring Functions (MLSF) to improve predictions. Therefore, it is crucial to develop models for pre-screening to direct rigorous tests.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] Of the handful of studies that have previously used EE for ligand binding, all have focused on the problem of computing absolute binding free energies (ABFE). 22,27,28 In the SAMPL4 host-guest challenge, Monroe et al showed that EE yields estimates comparable to other methods, in a system where molecular flexibility and multiple binding modalities are important. 27 Rizzi et al report similarly results in the recent SAMPL6 host-guest challenge.…”
Section: Introductionmentioning
confidence: 99%
“…27 Rizzi et al report similarly results in the recent SAMPL6 host-guest challenge. 28 To our knowledge, no group has published an example of relative binding free energy (RBFE) estimates predicted using EE. In theory, expanded ensemble simulations are particularly well-suited for absolute binding free energies, as the ligand is able to freely bind and unbind, sampling di↔erent binding modes.…”
Section: Introductionmentioning
confidence: 99%